Survey of knowledge of legal highs (novel psychoactive substances) amongst London pharmacists. Issue 2 (1st June 2015) - Guirguis, Amira; Corkery, John M.; Stair, Jacqueline L.; Kirton, Stewart; Zloh, Mire; Goodair, Christine M.; Schifano, Fabrizio; Davidson, Colin
Abstract : Purpose: – The purpose of this paper is to determine pharmacists' knowledge of legal highs (novel psychoactive substances (NPS)). Design/methodology/approach: – A questionnaire was handed out at two London pharmacist continuing education events in mid-2014. These events update pharmacists about developments of interest/relevance to the profession and to improve their practice. A total of 54 forms were returned; a response rate of 26 percent. Findings: – Most pharmacists had poor knowledge of NPS and many considered that NPS were not important to their work, with few having had to advise customers in this area. Despite this, the majority thought that they had insufficient information about NPS. There was a negative correlation between the age of the pharmacist and knowledge of NPS. Research limitations/implications: – The sample is a self-selected one drawn from registered pharmacists working in community pharmacies in northwest London, and thus does not include hospital pharmacies. Self-selection means that respondents may only reflect those who are interested in the NPS phenomenon and not the wider pharmacy community. The geographical area covered may not be representative of London as a whole, or indeed other parts of the UK or other EU countries. Practical implications: – It is clear that pharmacists do not know much about NPS but would like to know more. This information might improve their practice. Social implications: – Pharmacists, easier to see than general practitioners, could be a useful source of information for NPS misusers. Originality/value: – There have been no previous attempts to gauge the level of knowledge by pharmacists of legal highs/NPS in the UK or elsewhere to our knowledge.